Long-Acting Metformin Vs. Metformin Immediate Release in Patients With Type 2 Diabetes: A Systematic Review - Tan, Jixue; Wang, Yang; Liu, Song; Shi, Qingyang; Zhou, Xu; Zhou, Yiling; Yang, Xiaoling; Chen, Pingshan; Li, Sheyu (Frontiers in Pharmacology, 2021)
Background: Metformin, a commonly used anti-diabetic medication, is available in both an immediate-release (IR) formulation and a long-acting formulation (metformin extended-release; XR). Objective: We performed a systematic review to compare the effectiveness, safety, and patient compliance and satisfaction between the metformin IR and XR formulations. Method: We searched for randomized control trials (RCTs) and observational studies comparing the effectiveness, safety, or patient compliance and satisfaction of metformin XR with metformin IR using the MEDICINE, EMBASE, and Cochrane Central Register of Controlled Trials databases. Following report screening, data collection, and risk of bias assessment, we separately pooled data from RCTs and observational studies using the Grading of Recommendation Assessment, Development, and Evaluation approach to rate the quality of evidence. Result: We included five RCTs, comprising a total of 1662 patients, and one observational study, comprising 10,909 patients. In the meta-analyses, no differences were identified in outcomes of effectiveness and safety between the two forms of metformin (including change in HbA1c: mean difference [MD], −0.03%, 95% confidence interval [CI], −0.22% to 0.15%, fasting blood glucose: MD, −0.03 mmol/L, 95% CI, −0.22 to 0.15 mmol/L, postprandial blood glucose: MD, 0.04 mmol/L, 95% CI, −0.05 to 0.13 mmol/L, adverse events of abdominal pain: relative risk [RR], 1.15, 95% CI, 0.57 to 2.33, any adverse events leading to treatment discontinuation: RR, 1.51, 95% CI, 0.82 to 2.8, any gastrointestinal adverse events: RR, 1.09, 95% CI, 0.93 to 1.29, diarrhea: RR, 0.82, 95% CI, 0.53 to 1.27, flatulence: RR, 0.43, 95% CI, 0.15 to 1.23, nausea: RR, 0.97, 95% CI, 0.64 to 1.47, severe adverse events: RR, 0.64, 95% CI, 0.28 to 1.42, and vomiting: RR, 1.46, 95% CI, 0.6–3.56). Data from both the RCTs and the observational study indicate mildly superior patient compliance with metformin XR use compared with metformin IR use; this result was attributable to the preference for once-daily administration with metformin XR. Conclusion: Our systematic review indicates that metformin XR and IR formulations have similar effectiveness and safety, but that metformin XR is associated with improved compliance to treatment.